Application of 4STMD Method in Developing Colloid Chemistry Materials for Agricultural Product Processing Vocational Schools - Winda Fourthelina Sianturi; Sjaeful Anwar; Ijang Rohman; Nurlatifah (Universitas Negeri Medan, 2025)
Chemistry learning in Vocational High Schools (SMK), particularly in the Agribusiness Processing of Agricultural Products (APHP) expertise program, has not been fully integrated with vocational contexts, leading to students' low motivation and limited understanding of chemistry concepts. This study aims to develop a contextual chemistry learning module on colloidal systems using the Four Steps Teaching Material Development (4S-TMD) method. The research employed a Research and Development (R&D) approach following the DDE model (Design, Develop, Evaluate). The process included the design and initial development phases, namely selection and structuring stages. The selection phase resulted in five competency achievement indicators and ten concept labels compiled from 14 reference sources. The structuring phase produced a concept map, macro structure, and multi-level representations (macroscopic, sub-microscopic, and symbolic), all designed to enhance students' comprehensive understanding. The developed module shows potential in improving the relevance of chemistry instruction to vocational practices in SMK. Further research is recommended to proceed with the characterization and didactic reduction stages to optimize the readability and accessibility of the learning materials.